2021
DOI: 10.1016/j.celrep.2021.109108
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional and epi-transcriptional dynamics of SARS-CoV-2 during cellular infection

Abstract: Highlights d Infection dynamics are measurable by changes in proportion of subgenomic RNA (sgRNA) d SARS-CoV-2 produces multi-junction sgRNA, which can be TRS-dependent/independent d Viral sgRNA expression patterns change over the course of cellular infection d Modifications vary between genomic RNA and sgRNA but are steady throughout infection

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 39 publications
(42 reference statements)
7
44
0
Order By: Relevance
“…However, we observed the absence/low expression of ACE2 (< 5 reads per replicate) and TMPRSS2 (< 25 reads per replicate) genes across all our susceptible cell lines. The presence of these transcripts correlated with the viral burden observed in each cell line from our previous study (Data S1) (Chang et al, 2021).…”
Section: Cell-type Specific Changes In Host Gene Expression In Vitro Following Virus Infection Using Long-read Sequencingsupporting
confidence: 60%
See 2 more Smart Citations
“…However, we observed the absence/low expression of ACE2 (< 5 reads per replicate) and TMPRSS2 (< 25 reads per replicate) genes across all our susceptible cell lines. The presence of these transcripts correlated with the viral burden observed in each cell line from our previous study (Data S1) (Chang et al, 2021).…”
Section: Cell-type Specific Changes In Host Gene Expression In Vitro Following Virus Infection Using Long-read Sequencingsupporting
confidence: 60%
“…Publicly available data from our previous work (Chang et al, 2021) in combination with data generated from this study were analysed using Spartan (Meade, Lafayette, Sauter, & Tosello, 2017) et al, 2016) with the default direct RNA parameters '-ax splice -uf -k14 --secondary=no' and for all cDNA datasets '-ax splice -secondary=no'. All data were mapped to the respective combined transcriptome using the following parameters -'-ax map-ont'.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability to characterise viral transcriptomes with long-read sequencing has been especially useful throughout the COVID19 pandemic. Nanopore sequencing of the SARS-CoV-2 virus revealed the dynamic nature of transcription during its replication cycle (Chang et al, 2021). As well as identifying differential expression of subgenomic mRNA (sgRNA) transcripts during infection, novel sgRNAs containing non-canonical splice junctions were found that may have a role in enhancing viral protein production (Chang et al, 2021).…”
Section: Long Read Profiling Of Splicing In Diseasementioning
confidence: 99%
“…Nanopore sequencing of the SARS-CoV-2 virus revealed the dynamic nature of transcription during its replication cycle (Chang et al, 2021). As well as identifying differential expression of subgenomic mRNA (sgRNA) transcripts during infection, novel sgRNAs containing non-canonical splice junctions were found that may have a role in enhancing viral protein production (Chang et al, 2021). These studies focusing on viral infection highlight how long-read sequencing enables the detection of fulllength isoforms to reveal underlying viral mechanisms and further insight into the viral replication cycle within host human cells.…”
Section: Long Read Profiling Of Splicing In Diseasementioning
confidence: 99%